Lean Six Sigma Project Selection to Improve College Business Processes: Pemilihan Proyek Lean Six Sigma untuk Meningkatkan Proses Bisnis Perguruan Tinggi - Mulyana, Ig. Jaka; Gunawan, Ivan (Universitas Muhammadiyah Sidoarjo, 2024)
Higher education institutions are required to continuously improve the quality of their services to ensure institutional sustainability. Lean Six Sigma (LSS) offers a framework that integrates efficiency and quality improvement. This study aims to determine the priorities of LSS projects in higher education, considering the limited resources and the risk of project failure. The Analytical Hierarchy Process (AHP) and the Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods were used to determine priorities. The results showed that improving human resources (HR) and financial information systems is a strategic step. An integrated HR system supports the effective management of lecturers and education personnel, while an accountable financial system increases the transparency and efficiency of financial management. Both systems contribute to improving the quality of services to students. This research provides a basis for developing a digital transformation roadmap for higher education institutions.